Basic Motor Skills Profile of Badminton Athletes at a Legendary Club in Bandung - Kamilah Wulan Nurfitri; Ugelta, Surdiniaty; Williyanto, Septian (Universitas Negeri Semarang, 2025)
Introduction: The growing popularity of badminton globally underscores the importance of developing basic motor skills from an early age. Components such as speed, agility, balance, coordination, reaction time, and endurance are the main foundations that support an athlete's performance, especially in meeting the technical and physical demands of badminton. Objectives: This study aims to identify and describe the basic motor skills profile of 6 – 12 years old badminton athletes at the PB SGS PLN club in Bandung as a basis for evaluating and designing early age training programs. Method: This study used a quantitative descriptive approach with a cross-sectional design. The sample consisted of 35 athletes selected through purposive sampling. Basic motor skills were measured using six instruments: 10-meter sprint (speed), zig-zag run (agility), stork stand (balance), ball throw-catch (coordination), ruler drop test (reaction time), and beep test (endurance). Result: The results of the measurements show a consistent pattern of improvement in basic motor skills with increasing age. Older children demonstrate higher performance in all motor aspects compared to younger age groups, reflecting natural physical and neuromuscular development during the growth period. Conclusion: These findings emphasize the importance of designing training programs that are appropriate for children's developmental stages. In addition, the results of this study can be used as a practical reference for coaches in optimizing the training of young athletes in a gradual and targeted manner according to the age and motor skills of each individual.